El rol de la inteligencia artificial en la contabilidad moderna - Pacha Llambo, María Dolores (2024)
Artificial Intelligence has had a significant impact on a number of industries, and accounting is no exception. In the field of modern accounting, Artificial Intelligence is changing the way organisations manage their finances, optimise their accounting processes and make strategic decisions. That is why the objective of this research is focused on describing the role of Artificial Intelligence in modern accounting. The study will follow a qualitative- quantitative methodology to investigate the role of Artificial Intelligence in modern accounting. The research design will be non-experimental and descriptive, based on the collection and analysis of existing information from literature sources such as academic articles, books and papers. Among the main results of the use of Artificial Intelligence tools in accounting is the automation of accounting processes, reducing errors and time in tasks such as data entry and account reconciliation. Predictive analytics has improved financial projections and strategic decisions based on historical and market data. In addition, natural language processing has optimised the interpretation of unstructured data and the generation of reports, improving operational efficiency and business competitiveness. In conclusion, Artificial Intelligence is revolutionising accounting by improving efficiency, accuracy and transparency. Its implementation requires technological investment and training, but offers significant benefits for decision making and businesscompetitiveness.